White and brown rot fungal decay resistance of epoxy composite modified with nanocellulose and tetraethoxysilane - Hamid, Norul Hisham; Junedi, Mirratul Mukminah; Lipeh, Shahlinney; Jawaid, Mohammad; Ahmad Ludin, Norasikin; Abdullah, Ummi Hani; Daniel, Ahmad Azfar (North Carolina State University, 2024)
The resistance of epoxy composite modified with nanocellulose and tetraethoxysilane (TEOS) to decay by white rot (Trametes versicolor) and brown rot (Coniophora puteana) fungi was investigated using EN 113 (1996) as the guideline. The objective of this study was to investigate the effect of TEOS as a cross-linked agent in epoxy/nanocellulose composite, and its resistance against white rot and brown rot fungi. The epoxy resin was mixed with 10 wt% nanocellulose. The other three sets were prepared the same, but with the addition of 1%, 2%, and 3% TEOS for each set. All types of epoxy composites were air dried in a mold at ambient temperature for seven days followed by oven drying at 80 °C for 30 min. The composites were oven dried at 103 °C, sterilized, and exposed to the fungi at 22 °C for 16 weeks. It was found that the use of 1% to 3% TEOS in the composite reduced the percent weight loss following decay by T. versicolor, but not in the case of C. puteana. Overall, all types of the composite in this study were classified as highly durable and durable against the T. versicolor and C. puteana respectively. The surface and structure of all types of composites were still intact after 16 weeks of exposure period.